THE PROBLEM OF NORMATIVITY IN EXPLANATORY ENGLISH DICTIONARIES - Mukhamedganieva Malika Timurovna (Journals Park Publishing, 2023)
Due to the existence of the humanbeing’s need, it is natural phenomenon to set up normativity of explanatory dictionaries. The main reason for that is not only learner may encounter the problem in the interpretation of words, but also the words various usage. The article is devoted to assist the readers to find out the normativity and systems of dictionaries.
Keywords: Autonomous, explanatory word, alphabetical order, an etymological note, orthoepic, spelling, omonyms, homographs.